Application of Gene Therapy to Oral Diseases - Seiichi Yamano; Kenji Inoue; Yoichiro Taguchi (Pharmaceutics, 2025)
Gene therapy has emerged as a promising therapeutic approach across various oral diseases. This review examines current applications and future prospects of gene therapy in dentistry, focusing on five key areas: oral cancer, cancer-related pain, xerostomia (dry mouth), dental caries, and periodontal disease. Recent advances in viral and non-viral vectors have enabled more efficient gene delivery systems, with particular success in cancer pain management through µ-opioid receptor gene transfer and xerostomia treatment using aquaporin-1 gene therapy. For periodontal applications, gene therapy strategies include both immunomodulation and tissue regeneration approaches using growth factors like platelet-derived growth factor and bone morphogenetic proteins. While significant progress has been made, particularly in treating radiation-induced xerostomia and oral cancer pain, challenges remain in vector optimization and delivery methods. Clinical trials, predominantly in Phase I, indicate both the potential and current limitations of gene therapy in oral healthcare. This review synthesizes current evidence and outlines future directions for gene therapy applications in oral medicine and dentistry.